#TITLE_ALTERNATIVE# - EKANANDA (NIM 10503024), RIZKI
Electrical energy is one of the energy sources that commonly used in our lives. Unfortunately, most of the electrical energy consumed is generated from the burning of coal, oil, and natural gas, which definitely can cause severe pollution. Fuel Cell as one of the electrical energy source, have some benefits compare to other alternatives, thatÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’s include efficiency, portability, and emission produced. ThatÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’s why Fuel Cell have became a promising energy source alternative. In this research, a fluid dynamic simulation, namely Computational Fluid Dynamic (CFD), was conducted to see the effect of hydrogen flow in Polymer Electrolyte Membrane Fuel Cell (PEM-FC) to the current density and cell potential, which are some of the important parameters in determining Fuel Cell performance. The simulation was based on one of the Fuel Cell module at Center of Research in Physic PUSPITEK LIPI. The three dimensional model was created using Gambit software, while the CFD simulation was conducted using Fluent software. The output from CFD simulation then processed by mean of external software module so it can output the current density and cell potential data. Validation data was obtained by comparing simulation data with the actual measurement on the real Fuel Cell that was modeled. Hope this method can be enhance to handle more parameters to describe a diverse range of Fuel Cell condition, which will have the impact on the cost reduction and higher efficiency in the development process.